2020
DOI: 10.1186/s12884-020-2759-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gestational diabetes mellitus on risk of adverse maternal outcomes: a prospective cohort study in Northwest Ethiopia

Abstract: Background: Gestational diabetes mellitus is a leading medical condition woman encounter during pregnancy with serious short-and long-term consequences for maternal morbidity. However, limited evidence was available on potential impacts of gestational diabetes mellitus using updated international diagnostic criteria on adverse maternal outcomes. Therefore, this study aimed to assess the effects of gestational diabetes mellitus on the risk of adverse maternal outcomes in Northwest Ethiopia. Methods: A prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
72
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 70 publications
5
72
4
4
Order By: Relevance
“…3 An elevated blood glucose level during pregnancy is associated with adverse short-and long-term outcomes both for the mothers and their offspring. [4][5][6][7][8][9][10][11] Thus, identification of the associated risk factors is urgently required to prevent GDM.…”
Section: Introductionmentioning
confidence: 99%
“…3 An elevated blood glucose level during pregnancy is associated with adverse short-and long-term outcomes both for the mothers and their offspring. [4][5][6][7][8][9][10][11] Thus, identification of the associated risk factors is urgently required to prevent GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Although GDM often resolves after delivery, it is associated with long-lasting maternal and neonatal sequelae, such as increased risk of pregnancy-induced hypertension (PIH), cesarean delivery (CD), induction of labor, premature rupture of membranes (PROM), antepartum hemorrhage (APH), and postpartum hemorrhage (PPH). 4 9 In addition, GDM usually has long-lasting consequences, such as increased risk of type 2 diabetes (T2DM) and cardiovascular disease (CVD) in the mother, and future obesity, CVD, T2DM, and/or GDM in the child. 10 The psychological burden is also obvious in GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, timely diagnosis and treatment of GDM are needed. However, effective screening and diagnosis strategies for GDM are lacking in the world [ 5 ]. Studies have shown that fetal dysplasia may be related to the inhibitory effect of high-glucose environment on trophoblast cells.…”
Section: Introductionmentioning
confidence: 99%